Divergent seasonal responses of above- and below-ground to environmental factors in alpine grassland - Qin, Xiaojing; Nie, Xiaojun; Wang, Xiaodan; Hong, Jiangtao; Yan, Yan (Frontiers in Plant Science, 2023)
Introduction Under current global warming, the relationship between season changes of plants and environmental factors is focused on high-elevation and latitude regions. Due to the desynchronized growth of above- and below-ground and the buffering of soil, the driving factors in leaf and root show seasonal dynamics. Methods We measured above- and below-ground intensity in the alpine steppe over the non-growing season (October-April) and growing season (May-September). Air temperature, precipitation, soil moisture, and soil temperature were used to analyze the correlation based on the growth rhythm. Results Results showed that an earlier growth in spring and a delayed dormancy in autumn of root than leaf was observed. Our results strongly suggest that soil moisture plays a more important role in leaf unfolding while temperature is consistent with the withering of the shoots. Soil moisture comes from soil melt driving the spring phenology of roots, which derived from the storage of the subsoil layer in the last autumn. Discussion Climate change will affect the strong seasonal patterns that characterized these precipitation-limited systems, especially in the spring and fall shoulder seasons. As seasonality changes in the alpine steppe, divergent responses of leaf and fine root would be explored.